Análise da relação entre estratégia de manufatura e novas tecnologias e sua influência sobre o desempenho operacional - Finger, Andrew Beheregarai (Universidade do Vale do Rio dos Sinos, 2011)
This research paper examines how manufacturing strategy and supply chain planning (SCP) influence the anticipation of new technologies (ANT) and their effects on operational performance. We consider that manufacturing technology anticipation could be a source of competitive advantage based on the propositions of Hayes and Wheelwrigth (1984). The authors established that manufacturing can play at least four major roles in a firm’s competitive advantage, and in the last stage efforts are made to anticipate new manufacturing technologies for its future products. A theoretical model is proposed that links manufacturing strategy to supply chain planning. The model incorporates supplier partnership and function integration concepts in the relationship between manufacturing strategy and supply chain planning. In order to build the model, we used the constructs from the international research project High Performance Manufacturing (HPM). The data collection uses a survey methodology, and the data were analyzed with Structural Equation Modeling. As indicated in the literature, the data analysis show the positive and significant relationship between manufacturing strategy and ANT, with the manufacturing strategy the construct with the highest effect on the ANT among all the constructs considered. The findings indicate that the technological decisions related with cost and the rest of the competitive priorities do not share the same level of effect of their antecedents. The relationship between supply chain planning and ANT was found positive, but with less effect on ANT. The results show the weak direct effect from manufacturing strategy and SCP on performance, with SCP having a non significant effect on cost. Finally, the research contributes to operational management theory and practice showing that ANT are directed through manufacturing strategy and the firm’s could evaluate which impact the technologies will have on the competitive priorities, potentially bringing the trade-off concept. These findings demonstrate the importance of the ANT study for the competitive of the firm, especially because of its influence on operational performance and the clear importance of manufacturing strategy on this alignment, as stated by Hayes and Wheelwright (1984).
Keywords: Estratégia de manufatura; Planejamento da cadeia de suprimentos; Tecnologia de manufatura; Desempenho; Manufacturing strategy; Supply chain planning; Manufacturing technology; Operational performance; ACCNPQ::Ciências Sociais Aplicadas::Administração